Food oils as kairomones for trapping Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults. (December 2018) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.
Abstract: Insect infestation in the grain-based food in storage is often reported; Tribolium castaneum is a major pest. Determination of its population size using traps is entangled with the management attempts. Pheromone traps developed for T. castaneum often use kairomones with its aggregation pheromone 4, 8-dimethyldecanal (4, 8 DMD). However, low trapping efficacy is reported, and the information on promising kairomones is insufficient. The objective of this research was to evaluate the performance of some locally-available food oils as kairomones, alone and in combination with the pheromone for trapping T. castaneum adults. In the first experiment, the attraction of T. castaneum adults towards different food oils, the pheromone or the commercial kairomone was tested. In the second experiment, the attraction of T. castaneum to effective food oils + pheromone was determined under laboratory condition. In the third experiment, the attraction of T. castaneum by effective food oils + pheromone was evaluated under warehouse condition. Under laboratory condition, the highest attraction of T. castaneum adults was demonstrated by mee ( Madhuca longifolia ) and coconut ( Cocos nucifera ) oils. Either of these two oils when combined with the pheromone attracted more adults than the pheromone alone. Furthermore, attraction of T. castaneum adults by the two oils separately was similar to the commercially-available combination of pheromone and the kairomone. In contrast, under warehouse condition, the combination of mee oil and pheromone attracted T. castaneum adults similar to the commercially-available combination of pheromone and the kairomone. However, the attraction by the combination of coconut oil and pheromone was lower than that, and similar to the pheromone only. This study emphasizes the potential use of food oils as kairomones to trap T. castaneum adults, and augment the efficiency of pheromone traps available for this species. Highlights: Food oils were tested for their potential as kairomones for Tribolium castaneum. T. castaneum adults greatly responded to Cocos nucifera and Madhuca longifolia oils. Attraction by above oils was similar to 4, 8 DMD and commercially-available kairomone.